Negative association between 15 obesity- and lipid-related indices and testosterone in adult males: a population based cross-sectional study - Wei Guo; Shuo Zhao; Qinzheng Chang; Jiajia Sun; Yidong Fan; Jikai Liu (Lipids in Health and Disease)
Abstract Background An association exists between obesity and reduced testosterone levels in males. The propose of this research is to reveal the correlation between 15 indices linked to obesity and lipid levels with the concentration of serum testosterone, and incidence of testosterone deficiency (TD) among adult American men. Methods The study utilized information gathered from the National Health and Nutrition Examination Survey (NHANES) carried out from 2011 to 2016. The condition known as TD is typically characterized by a total serum testosterone level that falls below 300 ng/dL. The analysis used weighted linear and logistic regression methods to announce the association between 15 obesity- and lipid-related factors and serum testosterone levels as well as TD. Subgroup analyses were further carried out to confirm and validate the findings. Additionally, restricted cubic spline plots were utilized to examine non-linear relationships. Receiver operating characteristic (ROC) curves were created for the 15 factors, and the area under the curves (AUC) was calculated to assess the efficacy of each factor in detecting TD. Results Among a group of 3,540 adult males, it was observed that all 15 obesity- and lipid-related indices showed a negative relationship with testosterone concentration and a direct correlation with the presence of TD. After accounting for all covariates, the analysis revealed that individuals within the highest quartile (Q4) for metabolic score for visceral fat (METS-VF) had the excellent probability of developing TD (OR = 13.412, 95%CIs: 4.222, 42.262, P < 0.001). Additionally, a non-linear relationship was detected between the METS-VF with TD. Within the model that incorporated all adjustments, the triglyceride glucose-waist to height ratio (TyG-WHtR) has the best performance for predicting TD (Overall: AUC = 0.762, 95%CIs: 0.743, 0.782, cut-off = 5.186). Conclusion Elevated levels of these 15 markers were inversely related to testosterone levels and were indicative of an elevated risk of TD. Among all indices analyzed, TyG-WHtR demonstrated the highest predictive value. Trial registration Not available.